2021
DOI: 10.3389/fpsyg.2021.579183
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Properties of the Test of Passive Aggression

Abstract: Background: To date, most research on aggression in mental disorders focused on active-aggressive behavior and found self-directed and other-directed active aggression to be a symptom and risk-factor of psychopathology. On the other hand, passive-aggressive behavior has been investigated less frequently and only in research on psychodynamic defense mechanisms, personality disorders, and dysfunctional self-control processes. This small number of studies primarily reflects a lack of a reliable and valid clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 99 publications
4
17
1
Order By: Relevance
“…While the evidence for the latter hypothesis was convincing, the association between other-directed passive aggression and external anger-expression was only weak. Thereby, contradicting previous results that demonstrated a medium to strong association between TPA-OD and active aggression measured with the K-FAF ( Schanz et al, 2021 ). However, it remains unclear if these diverging results may be accounted for by methodological differences, differences in sample characteristics, or differences in assessed aggression types.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…While the evidence for the latter hypothesis was convincing, the association between other-directed passive aggression and external anger-expression was only weak. Thereby, contradicting previous results that demonstrated a medium to strong association between TPA-OD and active aggression measured with the K-FAF ( Schanz et al, 2021 ). However, it remains unclear if these diverging results may be accounted for by methodological differences, differences in sample characteristics, or differences in assessed aggression types.…”
Section: Discussioncontrasting
confidence: 99%
“…Self-directed aggressive behavior is assumed to be closely related to self-conscious emotions (Laye-Gindhu and Schonert-Reichl, 2005) and self-criticism (Gilbert et al, 2010). In line with this assumption, Schanz et al (2021) found an association between TPA-SD and an auto-aggressive mindset in a student sample, which requires a replication in an outpatient sample.…”
Section: Constructs For Evaluating the Validity Of The Tpamentioning
confidence: 81%
See 3 more Smart Citations